A spectroscopic atlas of Deneb (A2 lae) lambda lambda 3826-5212 - Albayrak, B.; Gulliver, A. E.; Adelman, S. J.; Aydin, C.; Koçer, Dursun (E D P SCIENCES, 7, AVE DU HOGGAR, PARC D ACTIVITES COURTABOEUF, BP 112, F-91944 LES ULIS CEDEXA, FRANCE, 2003)
We present a spectroscopic atlas of Deneb (A2 Iae) obtained with the long camera of the 1.22-m telescope of the Dominion Astrophysical Observatory using Reticon and CCD detectors. Forlambdalambda3826-5212 the inverse dispersion is 2.4 Angstrom mm(-1) with a resolution of 0.072 Angstrom. At the continuum the mean signal-to-noise ratio is 1030. The wavelengths in the laboratory frame, the equivalent widths, and the identifications of the various spectral features are given. This atlas should provide useful guidance for studies of other stars with similar spectral types. The stellar and synthetic spectra with their corresponding line identifications can be examined at ht tp://www.brandonu.ca/physics/gulliver/atlases.html.
Keywords: Atlases; Stars : Early type; Stars : Individual : Deneb; Stars : Supergiants